Fifteen-minute consultation: investigation and management of childhood epistaxis. Issue 1 (17th July 2014) - Siddiq, Somiah; Grainger, Joe
Abstract : Recurrent epistaxis is very common in children, and the majority of cases are self-limiting with simple first aid measures. However, recurrent episodes are a source of distress and anxiety for child and parent alike, and commonly result in hospital referral. We present a structured approach highlighting initial assessment, examination and management including when to refer to ear, nose and throat (ENT) surgery.